Ash deposition behaviors during combustion of raw and water washed biomass fuels. Issue 4 (August 2019) - Deng, Lei; Jin, Xi; Long, Jimiao; Che, Defu
Abstract: Biomass-fired boilers have the tendency to suffer from severe problems of fouling and slagging due to the high potassium content of biomass fuel. The troublesome potassium, however, can be removed efficiently by water washing pretreatment. In this study, the ash deposition behaviors during combustion of raw and water washed biomass fuels were investigated by a one-dimensional furnace and a deposition probe. Two biomass fuels (corn stalk and wheat straw) were used, and deposition mass, deposition efficiency, composition and morphology of the deposit were studied. The ash deposition while firing raw biomass exhibits a "fast−slow−fast−slow" trend with the sampling time. After water washing, the deposition mass decreases dramatically, and the deposition efficiency reduces gradually as the sampling time increases. The analyses of elemental composition, morphology and chemical composition on the deposit from raw biomass imply that the condensation/thermophoresis is quite significant in the earlier deposition stage, whereas the chemical reaction is remarkable in the later stage. After water washing, the potassium content of the deposit decreases significantly. Morphology and chemical composition analyses indicate that the deposit from water washed biomass ascribes to the physical accumulation of non-viscous fly ash particles. The deposition mass can easily approach a maximum value. The ash fusion temperatures of deposits increase remarkably after water washing. In addition, ash deposition mechanisms during biomass combustion are discussed. Highlights: The ash deposition exhibits a "fast−slow−fast−slow" trend with the sampling time. The ash deposition process of raw biomass was divided into four stages. The deposition mass and efficiency decrease after water washing. Deposit ascribes to physical accumulation of fly ash particles after water washing. The ash fusion temperatures of deposits increase remarkably after water washing.